Survival and central photopenia detected by fluorine-18 fluoro-deoxy-glucose positron emission tomography (FDG-PET) in patients with locoregional non-small cell lung cancer treated with radiotherapy. Issue 1 (July 2017) - Ashley Cox, Richard; Akhurst, Tim; Bressel, Mathias; MacManus, Michael; Ball, David
Abstract: Background: Primary non-small cell lung cancer cavitation and central photopenia, detected by radiology and FDG-PET scanning respectively, are thought to be the result of tumor necrosis. Such regions may contain hypoxic but viable carcinoma cells which may be relatively radioresistant compared with fully oxygenated regions. We hypothesized that photopenic tumors treated with radiotherapy with or without chemotherapy would be associated with worse survival compared with tumors not showing central photopenia. Patients and methods: The data were from a prospective trial (TROG 99-05) investigating the prognostic significance of primary tumor volume in patients receiving radical radiotherapy for locoregional non-small cell lung cancer (NSCLC). A subset of patients who had a pre-treatment FDG-PET scan formed the study population. The scans were evaluated by two observers for central photopenia in the primary tumor using a visual scoring system. The relationship of photopenia with survival was determined after adjusting for other prognostic factors. Results: There were 172 eligible patients. The two observers agreed on the presence of photopenia in 90% of cases (Kappa = 0.822, p < 0.001). Seventy-three patients were scored as having photopenia. Photopenia was not associated with worse survival, either on univariate analysis, or after adjusting for sex, performance status and nodal status (HR = 1.20, 95% CI 0.78–1.87, p = 0.4) Photopenia was however significantly associated with larger tumor volume and weight loss. Conclusions: This study failed to demonstrate a significantly worse survival associated with central photopenia in patients treated with radiotherapy for NSCLC.